PENERAPAN MULTIMEDIA DEVELOPMENT LIFE CYCLE DALAM MODEL PENGEMBANGAN PERMAINAN VR THE ARCHER - Haryanti, Marta Lenah; Chardaputeri, Gantari; Wangsa, Kesya; Figo, Russel; Indradjaja, Reynaldi; Sutanto, Kurniawan (Jurnal Algoritma, Logika dan Komputasi, 2025)
ABSTRACT Indonesia is one of the countries with the highest number of digital game users in the world. The development of Virtual Reality (VR) technology has brought increasingly immersive and realistic digital experiences. One of the applications of this technology is in the development of games that not only serve as entertainment but also function as training tools. This study aims to develop The Archer, a VR-based hunting game designed to enhance users' concentration and accuracy through interactive simulation. The development method used is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The development results show that The Archer performs well according to the designed specifications. Testing using the blackbox method indicates that all features, including menu navigation, player controls, scoring system, and interactions with Non-Playable Characters (NPCs), function optimally without any detected bugs. The use of 3D assets, natural sound effects, and an informative interface further enhances the realism and immersive experience of the game. This game has great potential as a medium to support cognitive and motor skill training. In addition to providing entertainment, The Archer can also be utilized as an effective training media.ABSTRAK Indonesia merupakan salah satu negara dengan jumlah pengguna permainan digital tertinggi di dunia. Perkembangan teknologi Virtual Reality (VR) telah menghadirkan pengalaman digital yang semakin imersif dan realistis. Salah satu pemanfaatan teknologi ini adalah dalam pengembangan permainan yang tidak hanya bersifat hiburan, tetapi juga berfungsi sebagai media pelatihan. Penelitian ini bertujuan untuk mengembangkan The Archer, sebuah permainan berburu berbasis VR yang dirancang untuk meningkatkan konsentrasi dan akurasi pengguna melalui simulasi interaktif. Metode yang digunakan dalam pengembangan permainan ini adalah Multimedia Development Life Cycle (MDLC), yang terdiri dari enam tahap: concept, design, material collecting, assembly, testing, dan distribution. Hasil pengembangan menunjukkan bahwa The Archer berjalan dengan baik sesuai dengan spesifikasi yang telah dirancang. Pengujian menggunakan metode blackbox menunjukkan bahwa seluruh fitur, termasuk navigasi menu, kontrol pemain, sistem skor, serta interaksi dengan Non-Playable Character (NPC), berfungsi optimal tanpa ditemukannya bug. Pemanfaatan aset 3D, efek suara alami, serta antarmuka yang informatif turut memperkuat kesan realistis dan imersif dalam permainan. Permainan ini memiliki potensi besar sebagai media pendukung latihan kognitif dan motorik. Selain memberikan hiburan, The Archer juga dapat digunakan sebagai alat bantu pelatihan.